1990
DOI: 10.2165/00003495-199040030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Recommendations for Topical Burn Therapy

Abstract: Infections in burn patients continue to be the primary source of morbidity and mortality. Topical antimicrobial therapy remains the single most important component of wound care in hospitalised burn patients. The goal of prophylactic topical antimicrobial therapy is to control microbial colonisation and prevent burn wound infection. In selected clinical circumstances topical agents may be used to treat incipient or early burn wound infections. At the present time silver sulfadiazine is the most frequently used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(71 citation statements)
references
References 30 publications
0
69
0
2
Order By: Relevance
“…Several studies have demonstrated the role of topical antimicrobials in decreasing morbidity and mortality in patients with major burn injuries (partial-or full-thickness skin involvement), particularly before early excision (189,298,307). A recent study conducted by the U.S. Army Burn Center compared the levels of mortality of adult patients according to age and burn size before (1950 to 1963) and after (1964 to 1968) the introduction of mafenide acetate topical antibiotic therapy (62).…”
Section: Prevention Of Burn Wound Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the role of topical antimicrobials in decreasing morbidity and mortality in patients with major burn injuries (partial-or full-thickness skin involvement), particularly before early excision (189,298,307). A recent study conducted by the U.S. Army Burn Center compared the levels of mortality of adult patients according to age and burn size before (1950 to 1963) and after (1964 to 1968) the introduction of mafenide acetate topical antibiotic therapy (62).…”
Section: Prevention Of Burn Wound Infectionsmentioning
confidence: 99%
“…Widespread application of an effective topical antimicrobial agent substantially reduces the microbial load on the open burn wound surface and reduces the risk of infection (189,298,307). By controlling infection, effective topical antimicrobial therapy decreases the conversion of partial-thickness to fullthickness wounds, but its use is adjunctive to early excision therapy.…”
Section: Topical Antimicrobial Therapymentioning
confidence: 99%
“…12,13,18,19 Silver-containing dressings have been marketed as bactericidal against a large number of gram-positive and gram-negative organisms for infants and children. 13 The results in the reduction of wound infections are mixed.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies done in vitro, the efficiency of silver sulphadiazine against Candida albicans was demonstrated. [6] IV.…”
Section: The Usage Areas Of Silver Nitrate In Dentistrymentioning
confidence: 99%
“…Silver chloride is photochemically activated by ultraviolet light and forms the colloidal pieces of metalic silver. The pieces occuring are seen as black and penetrates the epidermis [6].…”
Section: Picmentioning
confidence: 99%